Symptomatological, morphological, cultural and pathogenicity characters ofMycosphaerella pinodes from Himachal Pradesh - S. VINAY, C.L. BHARDWAJ and (Indian Phytopathology, 2002)
Pea samples with disease spots were collected from Bajaura, Himachal Pradesh, India, and the causal agent was identified as M. pinodes. Initial symptoms were small black flecks and pin head spots raised on pods, which enlarged into broad, concentric spots leading to foliage blight and yellowing. The spots common on leaves, stems and pods were ellipsoidal to circular with broad concentric rings and were light brown to dark brown in colour, sometimes purplish. Spots with irregular shape were common on sepals, petals and tendrils. The morphological characteristics of M. pinodes, are illustrated and discussed.